Bioresource availability and potential starch yield of sago stands in Mindanao, Southern Philippines - Oñez, John Paul E.; Estaña, Leo Manuel B.; Acosta, Joseph E.; Oponda, Nilo B. (2016)
In this chapter, we present our work on estimating the density of natural sago stands using line transect survey and assessing potential starch yield of palms in various growth stages from varying environmental (i.e., dry, wet, and submerged) and anthropogenic conditions (i.e., disturbed and undisturbed). Results of the line transect survey shows that sago palms are very dense in the provinces of Agusan del Sur and Agusan del Norte. More than 8000 palms are in the inflorescence stage, which can be harvested within one to two years; and more than 200,000 palms are in the hole formation stage, harvestable after four to five years. Results of the potential yield evaluation of sago palms show that those from wet environment and undisturbed by anthropogenic activities have the highest yield. By using our data on palm density, we can project a total of 2000 t of starch available from harvestable logs within one to two years and a total of 20,000 t within four to five years. These findings point to the potential of sago palm utilization as an economic enterprise for farmers in Mindanao.
Keywords: Sago palms -- Mindanao